Combustion synthesized hierarchically porous Mn3O4 for catalytic degradation of methyl orange. (16th November 2016) - Dong, Chengjun; Liu, Xu; Guan, Hongtao; Xiao, Xuechun; Wang, Yude
Abstract: Hierarchically porous Mn3 O4 has been synthesized via a facile solution combustion synthesis using Mn(NO3 )2  · 4H2 O as an oxidizer and ethylene glycolc (EG) as a fuel. The thermal analysis indicated that the combustion reaction can be initiated at a low temperature (126–140 °C). The obtained Mn3 O4 appeared as a hierarchical network with well‐connected poroes. At room temperature, the porous Mn3 O4 was found to be highly effective for catalytic degradation of methyl orange (MO) in the presence of acid. Abstract : A 3D porous Mn3 O4 possessed a coral‐like shape with a size of tens of micrometres and the hierarchically porous morphology has been prepared by a novel, rapid, and facile solution combustion synthesis, exhibiting an excellent degradation performance for methyl orange solution assisted by acid.